2007
DOI: 10.2110/jsr.2007.065
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variations in Modern Speleothem Calcite Growth in Central Texas, U.S.A.

Abstract: Variations in growth rates of speleothem calcite have been hypothesized to reflect changes in a range of paleoenvironmental variables, including atmospheric temperature and precipitation, drip-water composition, and the rate of soil CO 2 delivery to the subsurface. To test these hypotheses, we quantified growth rates of modern speleothem calcite on artificial substrates and monitored concurrent environmental conditions in three caves across the Edwards Plateau in central Texas. Within each of two caves, differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
164
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(179 citation statements)
references
References 19 publications
12
164
1
2
Order By: Relevance
“…(ii) High vertical extension rates are conducive to generating highresolution geochemical proxy datasets from stalagmites, yet to-date few studies have characterised stalagmite growth on intra-annual to decadal timescales and its implications for geochemical climate signal capture. (iii) Seasonal growth rate fluctuations potentially bias net proxy signals towards the season favourable to deposition (Baldini et al, 2008;Banner et al, 2007;Fairchild et al, 2006;Frisia et al, 2000;Mattey et al, 2008;Spötl et al, 2005). (iv) Growth rate variability may be related to climate signal modification by other processes, such as biomass change above the cave (e.g., Baldini et al, 2005) and surface and epikarst hydrology Bradley et al, 2010;Darling, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(ii) High vertical extension rates are conducive to generating highresolution geochemical proxy datasets from stalagmites, yet to-date few studies have characterised stalagmite growth on intra-annual to decadal timescales and its implications for geochemical climate signal capture. (iii) Seasonal growth rate fluctuations potentially bias net proxy signals towards the season favourable to deposition (Baldini et al, 2008;Banner et al, 2007;Fairchild et al, 2006;Frisia et al, 2000;Mattey et al, 2008;Spötl et al, 2005). (iv) Growth rate variability may be related to climate signal modification by other processes, such as biomass change above the cave (e.g., Baldini et al, 2005) and surface and epikarst hydrology Bradley et al, 2010;Darling, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has characterised their spatio-temporal variability at certain sites (Banner et al, 2007;) and, in particular, highlighted the importance of cave atmosphere pCO 2 dynamics for speleothem palaeoclimatology (Baldini et al, 2008;Fairchild et al, 2006). Although interpreting climatic variability from stalagmite morphology alone is challenging (Dreybrodt, 1988), understanding the physical controls on stalagmite growth, such as drop volume and dripwater film thickness, is necessary for proper linkage of local climate variability, cave environment systematics, and stalagmite growth behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the Wulu δ 13 C record most likely reflects the biogenic CO 2 production related to soil processes, although the confirmation of this interpretation via cave monitoring is currently restricted by deficit of active calcite deposition. Changes in the CO 2 degassing rate may also contribute to changes in the calcite δ 13 C [25], however, larger variations were only observed at the edge of stalagmites [13,26], sub-sampling along the central growth axis of stalagmite may effectively avoid this influence [27]. Even that the stochastic changes of CO 2 degassing contribute to the calcite δ 13 C, it can not result in the periodic variability observed in our record.…”
Section: Environmental Significance Of Stalagmite δ 13 Cmentioning
confidence: 65%
“…Spötl et al (2005) conducted pioneering work in the Obir Cave, Austria, and reported seasonal variation in the cave air P CO 2 as the main variable affecting CO 2 degassing and CaCO 3 precipitation from the drip water. Subsequent studies have revealed similar trends (e.g., Banner et al, 2007;Mattey et al, 2010;Boch et al, 2011;Wang et al, 2016), and the variation in P CO 2 has increasingly gained attention as an important variable controlling drip water kinetics.…”
Section: Introductionmentioning
confidence: 91%
“…As the cave air P CO 2 decreases, however, HCO 3 -and Ca 2+ gradually highlight the decreasing trend and the sequential differences. This might be caused by the incursion of outside air that lowers the air P CO 2 and promotes CO 2 degassing and CaCO 3 precipitation from the drip-water (Spötl et al, 2005;Banner et al, 2007;Boch et al, 2011). The pronounced differences of the WBD from SS3U are measured when the cave air P CO 2 was < 1,500 ppm, indicating that seepage water instantaneously outgasses CO 2 once it encounters low air P CO 2 , implying that the WBD contains a more accurate chemical signature within the carbonate rock matrix above the cave than the dripping water.…”
Section: Cave Air P Co 2 Vs Drip Rate On Drip Water Geochemistrymentioning
confidence: 99%